Athlete's screening for sudden cardiac death in different countries. History and recent days - O. S. Larintseva (National Electronic Information Consortium (NEICON), 2020)
Athletes with certain cardiovascular diseases have significantly increased risk of cardiac arrest and sudden cardiac death (SCD) during or after physical exertion. Therefore, the detection of pathological cardiovascular conditions is an important element of preparticipation screening in athletes. Athletes with complaints of syncopal or presyncopal conditions, dizziness during exercise or at rest, feelings of palpitations and interruptions in the work of the heart should be further examined before training. Questionnaire can help to identify these and other alarm medical conditions. The research is aimed to obtain information about cardiovascular screening questionnaires that are available in Russian and foreign sources, to compare questions, describing the current scientific view of the problem, identifying points of contention and moments requiring additional study. In general, modern screening strategies and those from past years correspond to each other and include similar issues that allow identifying sudden cardiac death risk factors in athletes.